Theory and craft of the scenographic model - Payne, Darwin Reid, 1931-2016.; Payne, Darwin Reid, 1931-2016. (Carbondale : Southern Illinois University Press, 1985)
Through diagrams, sketches, and models, along with explications of the essential tools and materials required, Payne defines and delineates the precise step-by-step procedures of scenographic modelmaking: the basic preparations of construction, the process of making the model, and the experimental aspects of modelmaking. This new edition with 50 additional illustrations and other new information offers teachers, students, and beginning professionals alike a complete and comprehensive approach to creating and constructing the scenographic model.
Revised edition of: Materials and craft of the scenic model. ©1976.
Includes bibliographical references (pages 151-156) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Theaters -- Models; Théâtres -- Modèles réduits.; PERFORMING ARTS -- Theater -- Stagecraft; Theaters -- Models; Bühnenbild; Modell